Expression profiling and sequence diversity of novel DREB genes from common bean (Phaseolus vulgaris L.) and their association with drought-related traits - Konzen, Enéas Ricardo (2016)
Common bean is a major dietary component in several countries, but its productivity is negatively affected by abiotic stresses. Dissecting candidate genes involved in abiotic stress tolerance is a paramount step toward the improvement of common bean performance under such constraints. Thereby, this thesis presents a systematic analysis of the DEHYDRATION RESPONSIVE ELEMENT-BINDING (DREB) gene subfamily, which encompasses genes that regulate several processes during stress responses, but with limited information for common bean. First, a series of in silico analyses with sequences retrieved from the P. vulgaris genome on Phytozome supported the categorization of 54 putative PvDREB genes distributed within six phylogenetic subgroups (A-1 to A-6), along the 11 chromosomes. Second, we cloned four novel PvDREB genes and determined their inducibility-factors, including the dehydration-, salinity- and cold-inducible genes PvDREB1F and PvDREB5A, and the dehydration- and cold-inducible genes PvDREB2A and PvDREB6B. Afterwards, nucleotide polymorphisms were searched through Sanger sequencing along those genes, revealing a high number of single nucleotide polymorphisms within PvDREB6B by the comparison of Mesoamerican and Andean genotypes. The nomenclature of PvDREB6B is discussed in details. Furthermore, we used the BARCBean6K_3 SNP platform to identify and genotype the closest SNP to each one of the 54 PvDREB genes. We selected PvDREB6B for a broader study encompassing a collection of wild common bean accessions of Mesoamerican origin. The population structure of the wild beans was accessed using sequence polymorphisms of PvDREB6B. The genetic clusters were partially associated with variation in latitude, altitude, precipitation and temperature throughout the areas such beans are distributed. With an emphasis on drought stress, an adapted tube-screening method in greenhouse conditions enabled the phenotyping of several drought-related traits in the wild collection. Interestingly, our data revealed a correlation between root depth, plant height and biomass and the environmental data of the location of the accessions. Correlation was also observed between the population structure determined through PvDREB6B and the environmental data. An association study combining data from the SNP array and DREB polymorphisms enabled the detection of SNP associated with drought-related traits through a compressed mixed linear model (CMLM) analysis. This thesis highlighted important features of DREB genes in common bean, revealing candidates for further strategies aimed at improvement of abiotic stress tolerance, with emphasis on drought tolerance